Bioacústica del canto de advertencia de Ceratophrys cranwelli (Anura: Ceratophrydae) Bioacoustic of the advertisement call of Ceratophrys cranwelli (Anura: Ceratophryidae) - Julián Alonso Valetti; Nancy Edith Salas; Adolfo Ludovico Martino (Revista de Biología Tropical, 2013)
El canto de advertencia en anuros es especie-específico, pero como los anfibios son organismos ectotermos, las variables acústicas pueden estar afectadas por la temperatura. Se describe el canto de advertencia de Ceratophrys cranwelli cuantificando el efecto de la temperatura sobre sus componentes. Los cantos se grabaron in situ y se registró la temperatura del sitio de canto. Un total de 54 cantos de 18 individuos fueron digitalizados y analizados. Las variables temporales de cada canto de advertencia fueron medidas a partir de los oscilogramas y sonogramas, mientras que el análisis de frecuencia se realizó a través del espectrograma. Mediante análisis de correlación múltiple se identificaron las variables acústicas temperatura-dependientes y el efecto de la temperatura fue cuantificado mediante los modelos de regresión lineal obtenidos. C. cranwelli posee un canto de advertencia simple pulsado. Las variables Duración del canto, Duración del pulso e Intervalo entre pulso decrecen con la temperatura, en tanto que la Tasa de pulsos está directamente correlacionada con la temperatura. Las variables temperatura-dependientes fueron estandarizadas a 25ºC según el modelo de regresión lineal obtenido para ser comparadas con datos publicados. Se demuestra la importante variabilidad que produce la temperatura en algunas propiedades del canto de C. cranwelli. The advertisement call plays an important role in the life history of anuran amphibians, mainly during the breeding season. Call features represent an important character to discriminate species, and sound emissions are very effective to assure or reinforce genetic incompatibility, especially in the case of sibling species. Since frogs are ectotherms, acoustic properties of their calls will vary with temperature. In this study, we described the advertisement call of C. cranwelli, quantifying the temperature effect on its components. The acoustic emissions were recorded during 2007 using a DAT record Sony™ TCD-100 with stereo microphone ECM-MS907 Sony™ and tape TDK™ DAT-RGX 60. As males emit their calls floating in temporary ponds, water temperatures were registered after recording the advertisement calls with a digital thermometer TES 1 300±0.1°C. Altogether, 54 calls from 18 males were analyzed. The temporal variables of each advertisement call were measured using oscillograms and sonograms and the analyses of dominant frequency were performed using a spectrogram. Multiple correlation analysis was used to identify the temperature-dependent acoustic variables and the temperature effect on these variables was quantified using linear regression models. The advertisement call of C. cranwelli consists of a single pulse group. Call duration, Pulse duration and Pulse interval decreased with the temperature, whereas the Pulse rate increased with temperature. The temperature-dependent variables were standardized at 25°C according to the linear regression model obtained. The acoustic variables that were correlated with the temperature are the variables which emissions depend on laryngeal muscles and the temperature constraints the contractile properties of muscles. Our results indicated that temperature explains an important fraction of the variability in some acoustic variables (79% in the Pulse rate), and demonstrated the importance of considering the effect of temperature in acoustic components. The results suggest that acoustic variables show geographic variation to compare data with previous works.